2020
DOI: 10.1038/s43247-020-00032-3
|View full text |Cite
|
Sign up to set email alerts
|

Significant contribution of small icebergs to the freshwater budget in Greenland fjords

Abstract: Icebergs represent nearly half of the mass loss from the Greenland Ice Sheet and provide a distributed source of freshwater along fjords which can alter fjord circulation, nutrient levels, and ultimately the Meridional Overturning Circulation. Here we present analyses of high resolution optical satellite imagery using convolutional neural networks to accurately delineate iceberg edges in two East Greenland fjords. We find that a significant portion of icebergs in fjords are comprised of small icebergs that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…The small contribution of subglacial discharge and direct glacier melt is supported by findings from other West Greenland fjords, which show that the majority of glacial modification takes place along the fjord -through, for example, iceberg melt -while direct melt from the glacier terminus and subglacial discharge are a small contributor (Mortensen et al, 2020;Muilwijk et al, 2021). Our model slightly underestimates the surface cooling and freshening, which we assume to be due to the exclusion of runoff to the surface of the fjord (Mernild et al, 2015), or possibly due to underestimated contribution from small icebergs by the power law size distribution (Rezvanbehbahani et al, 2020).…”
Section: Iceberg Modification In Ilulissat Icefjordmentioning
confidence: 84%
“…The small contribution of subglacial discharge and direct glacier melt is supported by findings from other West Greenland fjords, which show that the majority of glacial modification takes place along the fjord -through, for example, iceberg melt -while direct melt from the glacier terminus and subglacial discharge are a small contributor (Mortensen et al, 2020;Muilwijk et al, 2021). Our model slightly underestimates the surface cooling and freshening, which we assume to be due to the exclusion of runoff to the surface of the fjord (Mernild et al, 2015), or possibly due to underestimated contribution from small icebergs by the power law size distribution (Rezvanbehbahani et al, 2020).…”
Section: Iceberg Modification In Ilulissat Icefjordmentioning
confidence: 84%
“…In separate simulations, we assign maximum iceberg keel depths of 50 m, 150 m, 250 m, 350 m and 450 m, whilst maintaining the c1 concentration and the -2 power law exponent. We then vary the size-frequency distribution power law exponent from -1.6 to -2.1 in increments of 0.1 (covering the range observed to date in Greenland's fjords (Rezvanbehbahani et al, 2020;Sulak et al, 2017)), whilst retaining the c1 concentration and the 300 m maximum keel depth.…”
Section: Iceberg-ocean Interactionmentioning
confidence: 99%
“…Several recent studies have identified icebergs as a substantial freshwater source in some of Greenland's fjords, with iceberg freshwater volumes comparable to or greater than ice sheet runoff (Enderlin et al, 2016(Enderlin et al, , 2018Jackson and Straneo, 2016;Moon et al, 2017;Moyer et al, 2019;Rezvanbehbahani et al, 2020). Furthermore, modelling of one of these fjords suggests that including the heat and salt fluxes https://doi.org/10.5194/tc-2021-323 Preprint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tournadre and others, 2016; Sulak and others, 2017; Barbat and others, 2019; Neuhaus and others, 2019). Iceberg size distributions can yield a range of useful information: they provide insight on the fundamental processes driving iceberg calving (Benn and Åström, 2018; Cook and others, 2018); they can be useful for assessing iceberg risks to shipping and hydrocarbon infrastructure (Fuglem and others, 1996; Habib and others, 2016); iceberg size distributions have been shown to affect fresh water transport in global ocean models (Stern and others, 2016); and shifts in iceberg size distributions have the potential to alter the timing, magnitude and spatial distribution of ocean freshwater fluxes near glaciers and ice sheets (Enderlin and others, 2016; Rezvanbehbahani and others, 2020).…”
Section: Introductionmentioning
confidence: 99%